THE ANALYSIS OF THE READING MATERIALS IN “ENGLISH ON SKY 2” TEXTBOOK BASED ON SCHOOL-BASED CURRICULUM FOR GRADE VIII STUDENTS OF JUNIOR HIGH SCHOOL - Nurul Hidayah Siregar; Masitowarni Siregar (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2017)
This study attempts to describe the conformity between reading materials in English on Sky 2 Textbook for grade VIII students’ of junior high school and the requirements of School-Based Curriculum in the aspects of indicators, text types, social function, rhetorical structure, and linguistic features. It was designed as documentary analysis in the form of descriptive qualitative research. The data of this study were reading materials collected from English on Sky 2 Textbook published by Erlangga in 2007. Based on the analysis of those aspects, it was found that the aspect of indicators gains 81.66% conformity, the aspect of Text types gains 66.66% conformity as the six text types required by School-based Curriculum are not all presented in the textbook, the aspect of social function gains 37.5 % conformity, moreover, the aspect of rhetorical structure gains 100% conformity, and the aspect of  linguistic features gains 100% conformity. From the data obtained, the total conformity between the textbook and the requirements of School-based Curriculum attains 77.16% conformity. This number is categorized as  good according to Nurgiyantoro’s Criterion Referenced Evaluation. Therefore, this textbook is appropriate to be used by both teachers and students in English language teaching, particularly in teaching reading as this textbook has already followed the instructions and the requirements of School-based Curriculum. Key words: reading materials, textbook, School-based Curriculum